2015
DOI: 10.1016/j.compstruct.2015.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Continuous debonding monitoring of a patch repaired helicopter stabilizer: Damage assessment and analysis

Abstract: The present work focuses on the structural health monitoring of an aluminium vertical helicopter stabiliser with a pre-introduced crack which was repaired with an adhesively bonded composite patch. The structure was monitored under bending fatigue and its performance was evaluated with Lamb waves, lock-in thermography and ultrasonic testing. Outlier analysis of Lamb waves captured the onset and progress of the damage in the form of patch debonding, enabling the identification of five damage-severity regions. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…The demand for advanced composite structures in the modern industry is constantly growing as these materials offer many advantages compared to more conventional ones, especially in applications where high strength and stiffness to weight ratios are required. Thus, high performance composites are used widely in the fabrication of aircraft, automotive and marine structures . For example, new commercial aircrafts such as Boeing 787 and Airbus 350 XWB are the first commercial aircrafts to feature composites in fuselage primary structures .…”
Section: Introductionmentioning
confidence: 99%
“…The demand for advanced composite structures in the modern industry is constantly growing as these materials offer many advantages compared to more conventional ones, especially in applications where high strength and stiffness to weight ratios are required. Thus, high performance composites are used widely in the fabrication of aircraft, automotive and marine structures . For example, new commercial aircrafts such as Boeing 787 and Airbus 350 XWB are the first commercial aircrafts to feature composites in fuselage primary structures .…”
Section: Introductionmentioning
confidence: 99%
“…One of the most effective statistical measure is correlation coefficient [16]. It is one of the most often used both in laboratory experiments [17,18,19] and real structures applications [20,21,22]. Delaminations in composite materials are one of the most danger failure mode results typically from impact damage or manufacturing imperfections.…”
Section: Introductionmentioning
confidence: 99%
“…In a later study of the team, Grammatikos et al [15], the thermomechanical coupling observed in bonded repaired composites was studied in comparison with both acoustic emission signals and electrical measurements. More recently, the same principle was used in combination with Lamb waves technique, to study the bonded repair integrity of a patch repaired real helicopter wing by AgustaWestland (SW-4) [25].…”
Section: Thermomechanical Couplingmentioning
confidence: 99%
“…body (paint in this work ε = 0.97-1), ensures for optimum recording data and hence facilitates thermographic analysis [14,15,25,51].…”
Section: Sa Grammatikos Et Al Composite Structures 188 (2018) 461-469mentioning
confidence: 99%
See 1 more Smart Citation